Minat Kuliner Nusantara Pada Generasi Z (Studi Tentang Hubungan Keterpaan Informasi pada Konten Food Vlogger Youtube dengan Minat Kuliner Nusantara pada Generasi Z) - Adzra Bela Yumna; Ari Fadiati; Cucu Cahya (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to identify the relationship between information exposure to food vlogger content and interest in Indonesian culinary delights in Generation Z. This research uses a quantitative approach with a survey method. This research was conducted at the State University of Jakarta. The sample of this study were 10 Culinary Education students and used a purposive sampling method. There is a positive relationship between the information exposure variable on food vlogger content and the archipelago culinary interest variable in Generation Z.